Abiotic hydrogen generation from biotite-rich granite: A case study of the Soultz-sous-Forêts geothermal site, France - Murray, Jesica; Clément, Alain; Fritz, Bertrand; Schmittbuhl, Jean; Bordmann, Vincent; Fleury, Jean Marc (Applied geochemistry, 2020)
Investigations on geochemical processes involved in H2 generation in natural reservoirs are important for the present energy transition from fossil fuels. Most studies related to native H2 focus on the serpentinisation of ultra-mafic rocks, in which the source of H2 is linked to oxidation of Fe2+-bearing minerals and a reduction of H2O. In this study, we investigate abiotic H2 generation from a biotite-rich granite using an approach based on a study case of the Soultz-sous-Forêts geothermal site in France. Using a geochemical and reactive transport model and an existing database, we simulated the hydrothermal alteration of the granite at 130–200 °C with a redox potential from −100 mV to −300 mV. The simulations show that generation of native H2 is possible in an open system by hydrothermal alteration of biotite as a source of Fe2+, which oxidises to Fe3+ leading to precipitation of Fe3+ minerals and reduction of H+. The amount of H2 produced depends on the type of Fe2+/3+ minerals which precipitate. The optimal conditions for H2 generation are related to magnetite precipitation as in the serpentinisation process. We assessed that the upper bound for H2 production for this site is 102 kt per km3 of granite. This is in case of complete oxidation of all the ferrous iron contained in the biotite of the geothermal reservoir. In practice, only part of this potential may be attained owing to the limited current exploitation methods which are unlikely to result in a complete disequilibrium of the whole biotite. Future research needs to focus on how to reach most of the H2 potential. Simulations with increasing CO2 pressures suggest that CO2 injection can stimulate the H2 production. This study has implications for possible coupling of heat extraction and future exploitation with H2 production. •Native H2 can be generated by deep hydrothermal alteration of biotite-rich granite.•By chemical disequilibrium at 130–200 °C, Fe2+ oxidises to Fe3+, H+ reduces into H2.•Optimal conditions for H2 generation are related to magnetite precipitation.•The total potential for H2 production per km3 of granitic reservoir is 102 kt.•Artificial CO2 injection could stimulate H2 production.